1996
DOI: 10.1155/tsm.26-27.385
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Particles on Recrystallisation Textures and Microstructures

Abstract: The way in which large and small particles influence on recrystallised grain size and texture is considered with special emphasis on the processing of aluminium. It is well known that large particles might induce nucleation of recrystallised grains, while finely dispersed small particles will exert a pinning force on boundary movement. It the present paper, these two effects of particles will be discussed in detail. The discussion will to some extent be in an overview form, but also new ideas and recent experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Generally Si and Al 3 Fe particles precipitate during annealing of the cold-rolled alloy AA8011 [7]. Precipitation of particles at grain boundary affects the migration as well as shape of the boundary [25]. Vatne et al [25] have reported several characteristics of recrystallized grains like elongated, island and ragged shape grains owing to the effect of precipitates.…”
Section: Discussionmentioning
confidence: 99%
“…Generally Si and Al 3 Fe particles precipitate during annealing of the cold-rolled alloy AA8011 [7]. Precipitation of particles at grain boundary affects the migration as well as shape of the boundary [25]. Vatne et al [25] have reported several characteristics of recrystallized grains like elongated, island and ragged shape grains owing to the effect of precipitates.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1. Major components of the recrystallization texture for some particle containing alloys [58] The effect of PSN on recrystallization texture is as follows [59]:…”
Section: The Effect Of Particlesmentioning
confidence: 99%
“…It is already discussed in §4.8.2 that Al 3 Fe particles suppress the cube texture formation. Cube grain growth is also inhibited by "orientation pinning" [59].…”
Section: Effect Of Recrystallization Texture On Microstructure and Mementioning
confidence: 99%
See 1 more Smart Citation
“…Numerical models [29][30][31] accounting for recrystallization during and after hot deformation for aluminum alloys were developed, such as the ''Through Process Model'' for the production processes of aluminum [32]. It should be noted that, different from austenitic stainless steels, aluminum alloys are of high stacking fault energy and recrystallization is characterized by the gradual formation and appearance of a new structure with no identifiable nucleation and growth stages.…”
Section: Introductionmentioning
confidence: 99%